Genetic Diversity In Mango (Mangifera Indica L.) Through Multivariate Analysis - Majumder, DAN; Hassan, L; Rahim, MA; Kabir, MA (Bangladesh Journal of Agricultural Research, 2013)
The genetic divergence was assessed in 60 mango genotypes through D2- statistics and principal component analysis. The genotypes under study were grouped into eight clusters and the diversity was influenced by the morphological characters, not by the geographical distribution of the genotypes. The clustering pattern revealed that the genotypes collected from the same region did not fall in the single cluster. The maximum inter cluster distance was noticed between cluster II and cluster VIII, and the lowest between clusters VII and cluster VIII. From the cluster means, cluster I was high yielding and ranked first in terms of number of secondary branches per inflorescence, percent fruit set per inflorescence, and yield per plant. Cluster VIII had only one genotype which produced the highest percentage of flowering shoots, % perfect flowers, number of fruits per plant, and %TSS. The genotypes of cluster VII produced the biggest sized fruits. The first nine characters of the principal component axes with eigen values above unity accounted for 88.3% of the total variation among the fifteen characters. Weight of harvested fruits per plant (0.990 and 0.181), number of fruits per plant (0.101 and 0.607) and individual fruit weight (0.027 and 0.107) for both the vectors were positive across two axes indicating the important components of genetic divergence. The genotypes belonging to clusters I, VII and VIII with high to moderate genetic distances might be recommended for use in crossing programs to produce new recombinants with desired traits. Bangladesh J. Agril. Res. 38(2): 343-353, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15895